2022
DOI: 10.1002/cbin.11349
|View full text |Cite|
|
Sign up to set email alerts
|

Withdrawal: “Long Non‐coding RNA NEAT1 Drives the Development of Polycystic Ovary Syndrome via Sponging Multiple MicroRNAs” by Xia Sang and Yuzhen Zhang

Abstract: Schenkmann, and John Wiley & Sons Ltd. on behalf of the International Federation for Cell Biology. The withdrawal has been agreed because the authors could not be reached for fi nal approval of the publication of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…The initial finding from our research showed that NEAT1 and IGF1 were highly expressed while miR-381 was lowly expressed in PCOS. In line with the results in our study, a recent study highlighted that NEAT1 expression tended to upregulate in PCOS [9]. Similarly, NEAT1 was upregulated in tissues and cells of PCOS [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The initial finding from our research showed that NEAT1 and IGF1 were highly expressed while miR-381 was lowly expressed in PCOS. In line with the results in our study, a recent study highlighted that NEAT1 expression tended to upregulate in PCOS [9]. Similarly, NEAT1 was upregulated in tissues and cells of PCOS [9].…”
Section: Discussionsupporting
confidence: 92%
“…Of the lncRNA family, nuclear-enriched abundant transcript 1 (NEAT1) has been revealed to regulate ovarian carcinogenesis and act as a potential biomarker for antineoplastic therapies [7,8]. Moreover, NEAT1 has the ability to promote ovarian granulosa cell proliferation and suppress apoptosis through acting as a sponge of microRNAs (miRNAs) [9]. miRNAs that are differentially expressed in PCOS are related to the pathophysiology of the disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…***p < 0.001, **p < 0.01, and *p < 0.05 we identified miR-483 as a target of NEAT1, and the exogenous expression of NEAT1 reduced miR-483 expression, subsequently upregulating the expression of N-cadherin, Vimentin and Snail and promoting the EMT in osteosarcoma cells. Our results further confirmed the sponging of miR-483 by NEAT1, which has also been reported by Xia Sang in ovarian granulosa cells [48]. Using this mechanism, NEAT1 finely restrains the expression of miR-483 and promotes the proliferation and migration of osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, these three components constituted a network that regulates the EMT of osteosarcoma cells. Although our study is not the first study reporting the association between NEAT1 and miR-483 [48], it describes the regulation of STAT3 by miR-483 and their functions in regulating the EMT and metastasis of osteosarcoma cells for the first time. Our findings are also consistent with previous reports that overexpression of NEAT1 increases the proliferation, invasion and metastasis of oesophageal squamous cell carcinoma [49], while NEAT1 knockdown impairs cell invasion and migration and reduces the levels of EMTassociated proteins in renal cell carcinoma [50].…”
Section: Discussionmentioning
confidence: 92%
“…LncRNA ZFAS1 combining with miR-129 prevents miRNA-mediated degradation of HMGB1, inhibiting the proliferation activity while promoting the apoptosis of GCs (48). The expression of NEAT1 is upregulated in PCOS ovarian tissue, promoting the proliferation of human granulosa-like tumor cell line KGN via several miRNAs (i.e., miR-16, miR-483 and miR-324-3p) (47). However, whether the upregulated NEAT1 causes corpus luteum dysfunction in PCOS, like NEAT1 KO mice (38), is unclear.…”
Section: Cell Proliferation And/or Apoptosismentioning
confidence: 99%